The Effect of Mount Sinabung Volcanic Dust Mixture on The Strength of Construction Ceramics - Dosni Tahi Sipahutar (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
It has been made of construction ceramics using the volcanic dust of Mount Sinabung combined with kaolin, clay, feldspar and water as a mixture. with the composition of kaolin, feldspar, clay, volcanic dust of Mount Sinabung. Sample making is done starting with the sifting stage of 100 mesh materials and mixing materials up to homogeneous 15 minutes, printing with a 5 ton emphasis with a temperature combustion of 1100oc and in hold for 2 hours. With the characteristics of construction ceramics has been tested that is shrinkage mass 6.99-13.53%; porosity 4.84-10.46%; strong press 2.5-14.6 Mpa; hardness 84.7-169.6 kgf/mm2.